2018
DOI: 10.4269/ajtmh.17-0306
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enteropathy in Undernourished Pakistani Children: Clinical and Histomorphometric Analyses

Abstract: Abstract.Despite nutrition interventions, stunting thought to be secondary to underlying environmental enteropathy (EE) remains pervasive among infants residing in resource-poor countries and remains poorly characterized. From a birth cohort of 380 children, 65 malnourished infants received 12 weeks of nutritional supplementation with ready-to-use therapeutic food (RUTF). Eleven children with insufficient response to RUTF underwent upper endoscopy with duodenal biopsies, which were compared with U.S., age-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 31 publications
1
39
0
1
Order By: Relevance
“…Our data demonstrate similarities and differences between the cohorts that warrant comment. While EED and GSE cohorts share histopathologic similarities, as suggested by prior studies [26,40,[57][58][59][60], our index showed differences in the main histologic features that are classically associated with GSE, including intraepithelial lymphocytes. We also had the Environmental enteric dysfunction histology index opportunity to compare a GSE case from Pakistan (excluded from this analysis) whose total histologic score was somewhat less severe than the median scores of the St. Louis GSE cohort, although overall showed a similar pattern of tissue injury (detailed comparison of scores to St. Louis GSE and Pakistani cohorts in S4 Table).…”
Section: Environmental Enteric Dysfunction Histology Indexsupporting
confidence: 61%
See 3 more Smart Citations
“…Our data demonstrate similarities and differences between the cohorts that warrant comment. While EED and GSE cohorts share histopathologic similarities, as suggested by prior studies [26,40,[57][58][59][60], our index showed differences in the main histologic features that are classically associated with GSE, including intraepithelial lymphocytes. We also had the Environmental enteric dysfunction histology index opportunity to compare a GSE case from Pakistan (excluded from this analysis) whose total histologic score was somewhat less severe than the median scores of the St. Louis GSE cohort, although overall showed a similar pattern of tissue injury (detailed comparison of scores to St. Louis GSE and Pakistani cohorts in S4 Table).…”
Section: Environmental Enteric Dysfunction Histology Indexsupporting
confidence: 61%
“…We also had the Environmental enteric dysfunction histology index opportunity to compare a GSE case from Pakistan (excluded from this analysis) whose total histologic score was somewhat less severe than the median scores of the St. Louis GSE cohort, although overall showed a similar pattern of tissue injury (detailed comparison of scores to St. Louis GSE and Pakistani cohorts in S4 Table). A single case does not permit generalizations about the overlap between EED and GSE pathology, but raises the possibility that GSE disease may be distinguishable from EED by histopathology, as has been suggested in previous literature as well [26,40,57,59,60]. This may be most important in settings where both enteropathies co-exist.…”
Section: Environmental Enteric Dysfunction Histology Indexmentioning
confidence: 93%
See 2 more Smart Citations
“… 15 , 16 , 17 Environmental enteropathy and CD have been described as overlapping enteropathies. 17 , 18 , 19 , 20 , 21 Currently, the standard diagnostic criteria for these diseases is the evaluation of a small-intestinal biopsy obtained via an endoscopic procedure, which requires sedation. 17 , 22 Between 4 and 6 biopsies are required for diagnosis, 23 and because only parts of the bowel are affected in some cases, patients may require multiple endoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%